2017
DOI: 10.1111/ajt.14066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Allograft Injury Time of Onset on the Development of Chronic Lung Allograft Dysfunction After Lung Transplantation

Abstract: The impact of allograft injury time-of-onset on the risk of chronic lung allograft dysfunction (CLAD) remains unknown. We hypothesized that episodes of late-onset (≥6 months) allograft injury would produce an augmented CXCR3/ligand immune response, leading to increased CLAD. In a retrospective single-center study, 1894 transbronchial biopsies from 441 lung transplant recipients were reviewed for the presence of acute rejection (AR), lymphocytic bronchiolitis (LB), diffuse alveolar damage (DAD) and organizing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…We speculate that senescence reprogramming due to telomere dysfunction in club cells leads to release of an array of cytokines and chemokines that attract immune cells to the lung. Elevated numbers of T cells and NK cells could reflect a direct response to cell stress (37) or be due to T-cell attracting chemokines released by senescent club cells, such as CXCL-9, CXCL-10 and CXCL-11, that are commonly elevated in airway inflammation (38) and CLAD (39,40). Elevated levels of lymphocytes in lungs of SCGB1a1-cre TRF1 F/F transgenic mice suggests that telomere dysfunction in club cells could even contribute to the inflammatory changes seen in CLAD.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that senescence reprogramming due to telomere dysfunction in club cells leads to release of an array of cytokines and chemokines that attract immune cells to the lung. Elevated numbers of T cells and NK cells could reflect a direct response to cell stress (37) or be due to T-cell attracting chemokines released by senescent club cells, such as CXCL-9, CXCL-10 and CXCL-11, that are commonly elevated in airway inflammation (38) and CLAD (39,40). Elevated levels of lymphocytes in lungs of SCGB1a1-cre TRF1 F/F transgenic mice suggests that telomere dysfunction in club cells could even contribute to the inflammatory changes seen in CLAD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent single-center cohort study, we showed that late onset (at least 6 months posttransplant) LB is a risk factor for BOS, but not RAS. 128 However, in another study, LB was a risk factor for both BOS and RAS, and severe LB was more common in RAS than BOS. 149 As previously noted, the major risk factor for RAS is DAD, 114,115 and possibly OP as well.…”
Section: Mechanisms Of Clad Pathogenesis Injury and Dysregulated Repamentioning
confidence: 92%
“…115 Furthermore, BAL fluid concentrations of these chemokines are increased during injury, and the levels associate with the subsequent development of CLAD. 115,[128][129][130] CXCR3 chemokine ligands are also increased during community-acquired respiratory viral infection, and high levels predicted worse allograft function 6 months after recovery from the infection. 131 These studies suggest that CXCR3/ligand biology during allograft injury may set up the scenario for progression to CLAD by recruiting cytotoxic lymphocytes to the graft.…”
Section: Mechanisms Of Clad Pathogenesis Injury and Dysregulated Repamentioning
confidence: 99%
“…This is particularly concerning when compared with other solid organ transplants such as liver, kidney, and heart that have 5-year survival rates of at least 70% (1)(2)(3)(4)(5)(6). Lung transplant recipients also have much higher rates of rejection, the main risk factor for limited lung allograft survival (7)(8)(9)(10)(11)(12)(13)(14)(15). Rejection is classically considered a consequence of an immune response to donor alloantigens that results in allograft dysfunction (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Lung transplant recipients also have much higher rates of rejection, the main risk factor for limited lung allograft survival (7)(8)(9)(10)(11)(12)(13)(14)(15). Rejection is classically considered a consequence of an immune response to donor alloantigens that results in allograft dysfunction (7)(8)(9)(10)(11)(12)(13)(14)(15). However, many of the molecular factors involved in the initiation of the alloresponse that leads to rejection remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%